LAMTOR1 regulates dendritic lysosomal positioning in hippocampal neurons through TRPML1 inhibition - Sun, Jiandong; Lin, Weiju; Hao, Xiaoning; Baudry, Michel; Bi, Xiaoning (Frontiers in Cellular Neuroscience, 2024)
Intracellular lysosomal trafficking and positioning are fundamental cellular processes critical for proper neuronal function. Among the diverse array of proteins involved in regulating lysosomal positioning, the Transient Receptor Potential Mucolipin 1 (TRPML1) and the Ragulator complex have emerged as central players. TRPML1, a lysosomal cation channel, has been implicated in lysosomal biogenesis, endosomal/lysosomal trafficking including in neuronal dendrites, and autophagy. LAMTOR1, a subunit of the Ragulator complex, also participates in the regulation of lysosomal trafficking. Here we report that LAMTOR1 regulates lysosomal positioning in dendrites of hippocampal neurons by interacting with TRPML1. LAMTOR1 knockdown (KD) increased lysosomal accumulation in proximal dendrites of cultured hippocampal neurons, an effect reversed by TRPML1 KD or inhibition. On the other hand, TRPML1 activation with ML-SA1 or prevention of TRPML1 interaction with LAMTOR1 using a TAT-decoy peptide induced dendritic lysosomal accumulation. LAMTOR1 KD-induced proximal dendritic lysosomal accumulation was blocked by the dynein inhibitor, ciliobrevin D, suggesting the involvement of a dynein-mediated transport. These results indicate that LAMTOR1mediated inhibition of TRPML1 is critical for normal dendritic lysosomal distribution and that release of this inhibition or direct activation of TRPML1 results in abnormal dendritic lysosomal accumulation. The roles of LAMTOR1-TRPML1 interactions in lysosomal trafficking and positioning could have broad implications for understanding cognitive disorders associated with lysosomal pathology and calcium dysregulation.